How to help managing emotions felt by bipolar patients? - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2023)
The regulation of the control of the emotional experience is one of the determining parameters of the adaptation of an individual to his environment. Bipolar disorder is a psychiatric pathology in which disturbances in the processing of emotions are particularly marked during acute episodes and persist during the interictal period. Treatment with mood stabilizers generally improves the perception of emotions, while antidepressants are brakes on this perception. Finally, simple psychological measures can be useful in controlling emotions.